Tea marinating-induced improvement of quality in roasted chicken: The potential relationship between tea, flavor, and hazardous substances - Ji Wang; Jing Che; Xu-Song Wang; Lei Qin; Xu-Hui Huang (Food Chemistry: X)
The levels of flavor compounds and hazardous compounds are important indicators for evaluating high-temperature roasted food. In this paper, the effect of tea pre-marination on non-volatile compounds, volatile compounds, and hazardous compounds in roasted chicken. The results showed that the total content of key umami non-volatile compounds in roasted chicken marinated with green tea, white tea, and black tea increased by 17.43 % to 100.11 %. The content of alkenes, alcohols, aldehydes, and ketones in high-temperature roasted chicken marinated with oolong tea and yellow tea was increased. Different teas had varying inhibitory effects on hazardous compounds in high-temperature roasted chicken, while green tea exhibited the highest inhibition efficacy. The inhibition rates of green tea for ACY, 5-HMF, HCAs, and PAHs were 72.12 %, 69.87 %, 92.49 %, and 14.92 %, respectively. Flavonoids in tea may play an important role in the flavor enhancement and hazardous compounds inhibition of high-temperature roasted chicken.